2020
DOI: 10.1111/petr.13680
|View full text |Cite|
|
Sign up to set email alerts
|

Review of the impact of donor characteristics on pediatric heart transplant outcomes

Abstract: Heart transplantation (HTx) is a treatment option for end‐stage heart failure in children. HTx is limited by the availability and acceptability of donor hearts. Refusal of donor hearts has been reported to be common with reasons for refusal including preexisting donor characteristics. This review will focus on the impact of donor characteristics and comorbidities on outcomes following pediatric HTx. A literature review was performed to identify articles on donor characteristics and comorbidities and pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…6,15 In 2020, Conway and colleagues' meta-analysis of the characteristics of the ideal donor in pediatric heart transplantation, they found that the DRWR should be between 0.7 and 3 and that donor age should be <50 years old. 5 That same year, the ISHLT published a consensus statement describing donor organ acceptability criteria for pediatric heart transplantation. The ISLHT proposed to aim for a DRWR between 0.6 and 3.0 and, especially in adolescents, the organ should not come from a donor >5 years older, especially if the donor is >25 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,15 In 2020, Conway and colleagues' meta-analysis of the characteristics of the ideal donor in pediatric heart transplantation, they found that the DRWR should be between 0.7 and 3 and that donor age should be <50 years old. 5 That same year, the ISHLT published a consensus statement describing donor organ acceptability criteria for pediatric heart transplantation. The ISLHT proposed to aim for a DRWR between 0.6 and 3.0 and, especially in adolescents, the organ should not come from a donor >5 years older, especially if the donor is >25 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…There is no common agreement on the influence of weight mismatch, donor age, ABO compatibility, donor comorbidities, or infections on heart transplant outcomes in children. [5][6][7][8][9] Recently, the International Society of Heart and Lung Transplantation (ISHLT) published a consensus statement summarizing the scientific evidence on pediatric heart transplantation donor organ acceptability. 10 In our study, we focused on the ISHLT consensus statement recommendations that suggest donor organs should be less than 5 years older than the recipient and donor-recipient weight ratio (DRWR) should range between 0.6 and 3.0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of established standards or guidelines for pediatric heart assessment and subsequent acceptance may limit donor utilization with direct impact on waitlist outcomes. To address some of these issues, our center's experience prompted the development of the ISHLT pediatric consensus guidelines and the suite of papers recently published in Pediatric Transplantation 9‐17 …”
Section: Discussionmentioning
confidence: 99%
“…Among those who do survive to transplant, waitlist characteristics, including waitlist duration, available mechanical support options, and renal injury all contribute to post‐transplant outcomes 3‐8 . The waitlist phase of care has received considerable attention recently, including the recent publication of an International Society for Heart & Lung Transplantation (ISHLT) consensus statement on donor organ acceptability and other important papers 9‐19 …”
Section: Introductionmentioning
confidence: 99%